Cult Media
XI, 227 p. 7 illus. in color.
Keywords: This volume brings together writing on the topic of home media, and in particular releases described as appealing to ‘cult’ fans and audiences. Despite popular assumptions to the contrary, the distributors of physical media maintain a vivid presence in the digital age. Perhaps more so than any other category of film or media, this is especially the case with titles considered ‘cult’ and its related processes of distribution and exhibition. The chapters in this collection chart such uses and definitions of ‘cult’, ranging from home media re-releases to promotional events, film screenings, file-sharing and the exploitation of established fan communities. This book will be of interest to the ever-growing number of academics and research students that are specializing in studies of cult cinema and fan practices, as well as professionals (filmmakers, journalists, promoters) who are familiar with these types of films.